PENGARUH DURASI PENYIMPANAN WHOLE BLOOD TERHADAP JUMLAH TROMBOSIT PLATELET RICH PLASMA (PRP) - Aisyara Yuliandari (Jurnal Sains dan Teknologi Laboratorium Medik, 2020)
The number of platelets in Platelet Rich Plasma (PRP) is one of the factors that determine the quality of PRP. Whole blood is the main component in the manufacture of PRP. Improper handling of the whole blood can affect the number of thrombocytes in PRP. The study aim was to determine the effect of the whole blood storage duration on the platelet count of PRP. The design of this study used a post-test only control group design. The sample of this study was the whole blood from 8 male donors who had met the inclusion, and exclusion criteria. This study compared the PRP platelet counts processed from whole blood stored for 24 hours, and 48 hours compared to a control group/storage group for 0 hours. Platelets count data were analyzed using the one-way ANOVA test and followed by the Least Significant Difference (LSD) test using the SPSS version 22.0 program. PRP platelet count data are presented in tables and graphs. Based on statistical analysis, there was a significant decrease (p <0.05) between the PRP platelet counts in 24 hours storage group (132.937 platelets/µL) and the 48 hours storage group (91.000 platelets/µL) compared to the control group / 0-hour storage (702.437 platelets/µL). The duration of storing whole blood can affect the PRP platelet count, the longer the whole blood is stored, the lower the PRP platelet count will be. Keywords: Platelets, PRP, Storage duration, Whole blood